2021
DOI: 10.3390/nu13103409
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Intake, White Matter Integrity, and Neurodevelopment in Extremely Preterm Born Infants

Abstract: Background: Determining optimal nutritional regimens in extremely preterm infants remains challenging. This study aimed to evaluate the effect of a new nutritional regimen and individual macronutrient intake on white matter integrity and neurodevelopmental outcome. Methods: Two retrospective cohorts of extremely preterm infants (gestational age <28 weeks) were included. Cohort B (n = 79) received a new nutritional regimen, with more rapidly increased, higher protein intake compared to cohort A (n = 99). Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
0
15
1
Order By: Relevance
“…In our study protein intake did not have any relationship with either MDI or PDI scores and its intake was lower than recommended for extremely low birth weight infants, using standard fortification. Results from other studies focusing on protein intake are inconclusive-some authors report positive effect of protein on neurodevelopment [30,44], others report the opposite findings [50]. The latter study found that higher total protein intake resulted in lower motor scores at 2 years of CGA in ELBW infants, despite improved white matter integrity; however, the duration of parenteral nutrition in this study was longer than ours and parenteral protein may have played a role.…”
Section: Early Nutrient Intake and Neurodevelopmentcontrasting
confidence: 83%
“…In our study protein intake did not have any relationship with either MDI or PDI scores and its intake was lower than recommended for extremely low birth weight infants, using standard fortification. Results from other studies focusing on protein intake are inconclusive-some authors report positive effect of protein on neurodevelopment [30,44], others report the opposite findings [50]. The latter study found that higher total protein intake resulted in lower motor scores at 2 years of CGA in ELBW infants, despite improved white matter integrity; however, the duration of parenteral nutrition in this study was longer than ours and parenteral protein may have played a role.…”
Section: Early Nutrient Intake and Neurodevelopmentcontrasting
confidence: 83%
“…Human milk is not the only milk supplied nor breast feeding the only delivery method. Cow’s milk and enriched milk products are also utilized but human milk has many health inductive properties that make it more that nutritional and indeed more medicinal in nature [ 25 , 26 , 27 , 28 ]. Breastfeeding releases antioxidant and anti-inflammatory substances to the infant [ 29 ], helps establish the gut microbiome and the immune system [ 30 , 31 ] while promoting neurological development [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two small studies found positive associations of cumulative fat and energy intake with fractional anisotropy, but conflicted regarding the tract impacted; one found positive associations with the PLIC [ 13 ], while the other found associations with five white matter tracts (posterior corona radiata, thalamic radiations, superior longitudinal fasciculus, corticospinal tract, and superior corona radiata) but not the PLIC [ 14 ]. In addition, one study in extremely preterm infants found a positive association between higher protein—rather than fat—intake in the first week of life and FA in many of the same tracts as above, including portions of the corona radiata, thalamic radiations, superior longitudinal fasciculus, and internal capsule, plus the corpus callosum [ 40 ]. In contrast, we studied many of the same white matter tracts but found no association between macronutrient or energy intake and FA in any of the 15 tracts assessed.…”
Section: Discussionmentioning
confidence: 99%